An extension of Fuhrboter's studies for wave height: a theoretical study (Journal of Bangladesh Academy of Sciences, 2011)
This theoretical study extends Fuhrboter's work and includes the effects of air bubble entrainment. Result shows that there is a correlation between the sudden reductions of wave height and entrained of air bubbles into the water. Moreover, the study reveals that air entrainment occurs very short way in plunging breakers comparatively to spilling breakers. Key words: Fuhrboter's studies; Wave height; Theoretical study DOI: 10.3329/jbas.v34i2.6855Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 115-122, 2010